Studi Timbulan Dan Komposisi Sampah Sebagai Dasar Perencanaan Sistem Pengelolaan Sampah Di Kampus UIN SUSKA Riau - Aleksus Manurung; Ivnaini Andesgur; Tahrir Aulawi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
All human activities human will produce a residual in a form of solid called solid waste. UIN SUSKA Riau campus is a one of university in Pekanbaru with all of its activities is not hampered from solid waste production and problems coming from it, the solid waste accumulation for long days is some of problem coming out from the lack of intergrated solid waste management. This study aims to determine the waste generation and composition at UIN SUSKA Riau campus and planned waste management system that includes storage, collection, transportation in UIN SUSKA Riau campus. This study begins with the generation and waste composition studies conducted in 3 faculty, 3 offices, and 4 supporting fasilities. The study results showed the composition and in 2019 the daily waste generation of 556,28 kg/day in mass unit and 5.785 l/day in volume unit with generation is anorganic waste by 26,47% % and organic waste by 73,53%. Waste management planning in UIN SUSKA Riau campus include sorting unit with storage needs of 10 l bin for organic waste as much as 247 units and as many as 90 units of anorganic waste, bin capacity of 30 l to 139 units as much organic waste and anorganic waste as much as 50 units, bin capacity 60 l for organic waste as much as 41 units and 16 units of anorganic waste. Collection system in the form of segregated polling stations with a capacity of 1 m3. A transport fleet capacity of 4 m3 pick up 1 units.Keywords: generation and waste composition, waste management systems.